2008
DOI: 10.1007/s11095-008-9755-4
|View full text |Cite
|
Sign up to set email alerts
|

Intratracheal Versus Intravenous Liposomal Delivery of siRNA, Antisense Oligonucleotides and Anticancer Drug

Abstract: Purpose. To compare systemic intravenous and local intratracheal delivery of doxorubicin (DOX), antisense oligonucleotides (ASO) and small interfering RNA (siRNA). Methods. "Neutral" and cationic liposomes were used to deliver DOX, ASO, and siRNA. Liposomes were characterized by dynamic light scattering, zeta-potential, and atomic force microscopy. Cellular internalization of DOX, ASO and siRNA was studied by confocal microscopy on human lung carcinoma cells. In vivo experiments were carried out on nude mice w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
99
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 148 publications
(101 citation statements)
references
References 42 publications
1
99
1
Order By: Relevance
“…5B). Similar profiles of organ distribution were found also for DOX and liposomes (12). The calculation of content of ASO per gram tissue in different organs also showed their preferential accumulation in the lungs after inhalation administration (Fig.…”
Section: Resultssupporting
confidence: 80%
See 4 more Smart Citations
“…5B). Similar profiles of organ distribution were found also for DOX and liposomes (12). The calculation of content of ASO per gram tissue in different organs also showed their preferential accumulation in the lungs after inhalation administration (Fig.…”
Section: Resultssupporting
confidence: 80%
“…First, we had to incorporate neutral P-ethoxy modified antisense oligonucleotides and doxorubicin in one liposome; consequently, we had to use neutral liposomes because loading efficiency of neutral ASO and DOX into charged liposomes is low. Second, our previous data (12) showed that PEGylated neutral liposomes provided for the most favorable accumulation and retention of liposomes and their payload in the lungs after inhalation delivery.…”
Section: Methodsmentioning
confidence: 98%
See 3 more Smart Citations